Efforts to Improve Student Learning Outcomes from a Scientific Approach to the Theme of Growth and Development of Living Things in Class III of SDN Banyumekar, Labuan District, Pandeglang Regency - Fadhlan Prasetyo; Fitria Diningsih; Fajrin Yuningsih; Rika Amelia; Hanawati; Andri Subekhi (Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The purpose of this study was to determine how Nuraeni (2017:15) the use of the scientific approach could improve the learning outcomes of third-grade students at SDN Banyumekar, Labuan District, on the subject of the growth and development of living things. This study is a Classroom Action Research (CAR) conducted in two cycles, with 22 students in the class involved in the planning, implementation, observation, and reflection stages.  III SDN Banyumekar in the 2020–2021 academic year. The methods used to collect data included observation, interviews, learning outcome tests, questionnaires, and information. The results of the study emphasised that the application of the scientific method can significantly improve school academic outcomes. The average learning outcome score increased from 56.96 in the pre-cycle to 71.81 in cycle I and 85.45 in cycle II. This improvement was also accompanied by an increase in student learning activities, particularly in terms of paying attention, asking questions, trying, debating, and communicating observation results. Thus, it can be concluded that the application of the scientific method improved student learning outcomes in the subject of growth and development of living things at SDN Banyumekar, Labuan District, in the 2020–2021 academic year.